Androgen receptor coregulator long noncoding RNA CTBP1-AS is associated with polycystic ovary syndrome in Kashmiri women - Nabi, Mudasar; Andrabi, Syed Mudasir; Rasool, Shayaq Ul Abeer; Ashraf, Sairish; Majid, Imran; Amin, Shajrul (Endocrine, 2022)
Objective Polycystic ovary syndrome (PCOS) is one of the most common reproductive, endocrine, and metabolic disorder in premenopausal women. Even though the pathophysiology of PCOS is complex and obscure, the disorder is prominently considered as the syndrome of hyperandrogenism. C-Terminal binding protein 1 antisense (CTBP1-AS) acts as a novel androgen receptor regulating long noncoding RNA (lncRNA). Therefore, the present study was aimed to establish the possible association of androgen receptor regulating long noncoding RNA CTBP1-AS with PCOS. Methods A total of 178 subjects including 105 PCOS cases and 73 age-matched healthy controls were recruited for the study. The anthropometric, hormonal, and biochemical parameters of all subjects were analyzed. Total RNA was isolated from peripheral venous blood and expression analysis was done by quantitative real-time PCR. The correlation analysis was performed to evaluate the association between and various clinical parameters and lncRNA CTBP1-AS expression. Results and conclusion The mean expression level of CTBP1-AS was found to be significantly higher in the PCOS women than in the healthy controls (-lnCTBP1-AS, 4.23 ± 1.68 versus 1.24 ± 0.29, P < 0.001). Furthermore, subjects with higher expression level of CTBP1-AS had significantly higher risk of PCOS compared to subjects with low levels of CTBP1-AS expression (actual OR = 11.36, 95% CI = 5.59–23.08, P < 0.001). The area under receiver operator characteristic (ROC) curve was 0.987 (SE 0.006, 95% CI 0.976–0.99). However, lncRNA CTBP1-AS was found to have no association with different clinical characteristics of PCOS. In conclusion, androgen receptor coregulating lncRNA CTBP1-AS is associated with PCOS women and high expression of CTBP1-AS is a risk factor for PCOS in Kashmiri women